IDH1 mutation in human glioma induces chemical alterations that are amenable to optical Raman spectroscopy - Uckermann, Ortrud; Yao, Wenmin; Juratli, Tareq A.; Galli, Roberta; Leipnitz, Elke; Meinhardt, Matthias; Koch, Edmund; Schmitz-Schackert, Gabriele; Steiner, Gerald; Kirsch, Matthias (Journal of neuro-oncology, 2018)
Mutations in the isocytrate dehydrogenase 1 (IDH1) gene are early genetic events in glioma pathogenesis and cause profound metabolic changes. Because this genotype is found in virtually every tumor cell, therapies targeting mutant IDH1 protein are being developed. The intraoperative administration of those therapies would require fast technologies for the determination of IDH1 genotype. As of today, there is no such diagnostic test available. Recently, infrared spectroscopy was shown to bridge this gap. Here, we tested Raman spectroscopy for analysis of IDH1 genotype in glioma, which constitutes an alternative contact-free technique with the potential of being applicable in situ.
Gesehen am 19.02.2020